EFFECTIVENESS OF THE DEEP LEARNING APPROACH IN ENHANCING STUDENTS' CRITICAL THINKING SKILLS ON MATRIX MATERIAL - Kintoko Kintoko; Stevanus Budi Waluya; Deny Hadi Siswanto (Jurnal Karya Pendidikan Matematika, 2025)
This study investigates the effectiveness of the Deep Learning approach in enhancing students' critical thinking skills in matrix material. The approach emphasizes deep understanding, enabling students to analyze, interpret, and connect concepts comprehensively. A quasi-experimental design with a nonequivalent control group was employed, involving tenth-grade students at Muhammadiyah Kalasan Senior High School. The research sample consisted of two classes: the experimental class (X-A), which applied the Deep Learning approach, and the control class (X-B), which used conventional teaching methods, with 28 students in each group. To evaluate learning improvement, both groups took a pretest before treatment and a posttest afterward. Data analysis utilized an independent sample t-test to test the hypothesis and an n-Gain test to assess critical thinking skill improvement. Results indicated a significant increase in students' critical thinking abilities, with the experimental group outperforming the control group (sig. 0.000 < 0.05). The highest improvement was in the Situation aspect (56.43), while the Overview aspect showed the least growth (6.43). The average score increased from 55.71 to 86.18, with an N-Gain of 0.68 (moderate category). Further research could explore this approach in different subjects to enhance educational quality